New species of Homidia (Collembola: Entomobryidae) from Yunnan, China: morphology, DNA barcodes and first instar characteristics - Ding, Yin-Huan; Li, Gui-Zhao; Lu, Jin-Cheng; Zhang, Feng (Zootaxa, 2026)
This study formally describes a new species of Homidia Börner from Yunnan, China. Homidia quadripora sp. nov. is distinctly characterized by its purple body pigmentation, a V-shaped unpigmented area on the head, a lighter purple patch in the middle on the posterior half of the forth abdominal segment, four M-series mac-chaetae on the head, four pseudopores on the coxae of the mid leg, and a mac-chaeta m5 on the first abdominal segment. Comparative morphological and molecular analyses (using COI sequences) with phenotypically similar Homidia species corroborate its distinctiveness and support its designation as a new species. Furthermore, this research offers a crucial description of its first instar characteristics, comparing them with adult features and early stages of other Homidia species to illustrate developmental changes and differences.